Composition of essential oils of four Hedychium species from Vietnam - Van Thanh, Bui; Dai, Do N; Thang, Tran D; Binh, Nguyen Q; Anh, Luu D Ngoc; Ogunwande, Isiaka A (BMC chemistry, 2014)
Vietnam is a country blessed with many medicinal plants widely used as food and for medicinal purposes, and they contain a host of active substances that contribute to health. However, the analysis of chemical constituents of these plant species has not been subject of literature discussion. In this study, the chemical compositions of essential oils of four Hedychium species, obtained by hydrodistillation, were determined by means of gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS) techniques. Individually, α-pinene (52.5%) and β-pinene (31.8%) were present in the leaf oil of Hedychium stenopetalum Lodd., while linalool (45.2%), (E)-nerolidol (8.7%) and α-pinene (5.0%) were identified in the root. The leaf of Hedychium coronarium J. König was characterized by β-pinene (20.0%), linalool (15.8%), 1,8-cineole (10.7%), α-pinene (10.1%) and α-terpineol (8.6%); while β-pinene (23.6%), α-humulene (17.1%) and β-caryophyllene (13.0%) were identified in the root. Hedychium flavum Roxb., gave oil whose major compounds were β-pinene (22.5%), α-humulene (15.7%) and β-caryophyllene (10.4%) in the leaf; α-humulene (18.9%), β-caryophyllene (11.8%) and β-pinene (11.2%) in the stem, as well as β-pinene (21.8%), linalool (17.5%) and 1,8-cineole (13.5%) in the root. The main constituents of Hedychium ellipticum Buch.-Ham. ex Smith were (E)-nerolidol (15.9%), β-pinene (11.8%) and bornyl acetate (9.2%) in the leaf with 1,8-cineole (40.8%), α-pinene (18.3%) and β-pinene (11.0%) occurring in the root. Ubiquitous monoterpenes and sesquiterpenes were identified as characteristic markers for Hedychium species. This work is of great importance for the evaluation of Hedychium essential oils grown in Vietnam.